Xylanase Impact beyond Performance: Effects on Gut Structure, Faecal Volatile Fatty Acid Content and Ammonia Emissions in Weaned Piglets Fed Diets Containing Fibrous Ingredients - Waewaree Boontiam; Pheeraphong Phaenghairee; Veerle Van Hoeck; Bindhu Lakshmibai Vasanthakumari; Ingrid Somers; Alexandra Wealleans (Animals, 2022)
The addition of xylanase to piglet diets is known to improve performance and nutrient digestibility. The present study aimed to assess the impact of new xylanase on the growth performance, nutrient digestibility, and gut function of weaned piglets. A total of 144 pigs, weaned at 28 days (7.48 kg initial body weight, IBW), were assigned to 36 pens and 9 pens per treatment. Dietary treatments were a basal complex control diet, and the basal diet supplemented with 45,000, 90,000 and 135,000 U/kg xylanase. Performance was measured at days 0, 14 and 35. At day 35, samples were collected for assessment of intestinal histology, and volatile fatty acid and ammonia concentrations. After two weeks post-weaning, additional 12 piglets (11.34 kg IBW) were placed in metabolic crates for assessment of apparent total tract nutrient digestibility using a dietary marker. The addition of xylanase at 90,000 and 135,000 U/kg significantly improved average daily gain (333.6 g/day control, 364.86 g/day, 90,000 U/kg, 405.89 g/day, 135,000 U/kg, p < 0.05), G:F (0.557 control, 0.612 90,000 U/kg, 0.692 135,000 U/kg, p < 0.05), and reduced diarrhoea. This was driven improved nutrient digestibility and villus height in the jejunum (372.87 µm control, 432.53 µm 45,000 U/kg, 465.80 µm 90,000 U/kg, 491.28 µm 135,000 U/kg, p < 0.05). Xylanase supplementation also linearly increased faecal butyrate levels and had a quadratic relationship with propionate concentrations. 135,000 U/kg xylanase also reduced ammonia emissions. In conclusion, dietary supplementation with xylanase improved growth performance and feed efficiency in weaning piglets, likely driven by improvements to gut structure and function.